Establishing rates of carbon sequestration in mangroves from an earthquake uplift event - Salmo, Severino G, III (Archīum Ateneo, 2019)
We assessed the carbon stocks (CS) in mangroves that developed after a magnitude 7.1 earthquake in Silonay, Oriental Mindoro, south Luzon, The Philippines in November 1994. The earthquake resulted in a 50 cm uplift of sediment that provided new habitat within the upper intertidal zone which mangroves colonized (from less than 2 ha pre-earthquake to the current 45 ha, 23 years post-earthquake). The site provided an opportunity for a novel assessment of the rate of carbon sequestration in recently established mangroves. The carbon stock was measured in above-ground, below- ground and sediment compartments over a seaward to landward transect. Results showed a mean carbon stock of 549 ± 30 Mg C ha-1 (of which 13% was from the above-ground biomass, 5% from the below-ground biomass and 82% from the sediments). There was high carbon sequestration at a 40 cm depth that can be inferred attributable to the developed mangroves. The calculated rate of C sequestration (over 23 years post-earthquake) was 10.2 ± 0.7 Mg C ha -1 yr-1 and is comparable to rates reported from man- groves recovering from forest clearing. The rates we present here from newly developed mangroves contributes to calibrating estimates of total CS from restored mangroves (of different developmental stages) and in mangroves that are affected by disturbances.